1997
DOI: 10.1179/mst.1997.13.8.679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of friction weld interface of aluminium to austenitic stainless steel joint

Abstract: A type 1050 commercial aluminium was bonded to a type 304 austenitic stainless steel using a continuous drive friction welding process. The bonding interface conditions were evaluated by means of mechanical tests, to measure tensile and bending properties, and ultrasound microscopic observation. The tensile strength of the joints increased as the frictional time increased. High strength joints could be obtained at africtional time greater than 0·2 s. However, ultrasound microscopy clearly showed that bonding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 8 publications
(2 reference statements)
1
24
0
Order By: Relevance
“…Reddy et al [9] reported that using an Ag interlayer during friction welding of stainless steel to 1050 aluminum alloy provided the possible formation of FeAl in addition to Fe 2 Al 5 . Similarly, Fukumoto et al [10,11] reported that mainly Fe 2 Al 5 formed and Fe 3 Al and FeAl might have been formed during friction welding of non-heat treatable 1050 aluminum alloy to stainless steel. Published studies are mainly concentrated on dissimilar Al-Fe friction welding of aluminum, especially 1xxx series alloys, to stainless steels.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reddy et al [9] reported that using an Ag interlayer during friction welding of stainless steel to 1050 aluminum alloy provided the possible formation of FeAl in addition to Fe 2 Al 5 . Similarly, Fukumoto et al [10,11] reported that mainly Fe 2 Al 5 formed and Fe 3 Al and FeAl might have been formed during friction welding of non-heat treatable 1050 aluminum alloy to stainless steel. Published studies are mainly concentrated on dissimilar Al-Fe friction welding of aluminum, especially 1xxx series alloys, to stainless steels.…”
Section: Introductionmentioning
confidence: 95%
“…If properly applied, friction welding and its variant inertia friction welding provides joining at relatively low temperatures with an overall short thermal cycle. Recent research has addressed friction welding material combinations including mainly pure and alloyed aluminum to stainless steel [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional fusion welding methods, such as arc and laser heating have been used to join aluminum and steel [2,5,6]; however, the poor seam surface of the weld and the formation of porosity in the weld hinder the practical applications of these two techniques. Friction welding has been proven practical to eliminate the formation of the intermetallic phases and to form a sound weld [3,7,8], but this method is usually used for joining cylindrical parts. As a newly emerging technology, friction stir welding (FSW), which has been widely applied in the industry for joining aluminum alloys and is expanding its application in joining steels [9,10], is expected to provide a practical solution for joining aluminum-steel.…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned that the formation of intermetallic compound needed enough heat or friction time to obtain. Although the formation of a certain amount of intermetallic reaction product is necessary to obtain high quality joint strength, an excess of the intermetallic reduces the joint strength to below practical usable values (Fukumoto et al, 1997). It has been suggested that intermetallic formation at joint interface is an essential requirement for the attainment of satisfactory bond formation during dissimilar friction welding (Fuji et al, 1997).…”
Section: Resultsmentioning
confidence: 99%